Assessment of mixed mode loading on macroscopic fatigue crack paths in thick section Al–Cu–Li alloy plate. (5th March 2016) - Joyce, M.R.; Starink, M.J.; Sinclair, I.
Abstract: High strength, wrought 7xxx (Al – Zn – Mg) and Al – Li based alloys show a propensity for fatigue macroscopic crack deflections aligned along grain boundaries. The present work reports a study on a 3rd generation Al – Li based alloy in the form of a thick AA2297 (Al – Cu – Li alloy) plate, where it was found that although the lithium containing material may indeed be more susceptible to mixed mode grain boundary failure (and by implication crack deflection in conventional tests), the AA2297 alloy fatigue behaviour is mechanistically and functionally equivalent to 7xxx alloy behaviour. It is shown that crack paths are controlled by a combination of crack loading mixity ( K II / K I ratio) and maximum strain energy release rates (expressed as K eq.max ). Increasing K II / K I ratio is seen to favour sustained grain boundary failure. Crack growth rate behaviour is discussed in terms of extrinsic and intrinsic components of crack growth resistance. It is shown that the present approach can be successfully applied to predict crack deflection/crack paths for a range of sample geometries and orientations on a range of high strength orthotropic aluminium alloys, including 3rd generation Al – Li based alloys and well-established 7xxx alloys). Graphical abstract: Highlights: Wrought Al-7xxx and Al–Li based alloys show fatigue macroscopic crack deflections. Third generation rolled Al–Li alloy AA2297 is susceptible to sustained crack deflections. Crack deflection is aligned with the grain boundaries. Local crack direction is controlled by loading mixity and maximum strain energy release. A consistent approach to analysing and predicting crack deflections is provided.